Decolonizing and indigenizing visions of educational leadership : global perspectives in charting the course - Wane, Njoki N.; Todd, Kimberly L.; Chau, Coly; Watts, Heather (Emerald Publishing Limited, 2022)
This edited collection centres the reclamation of global counter and Indigenous knowledges, epistemologies, ontologies, axiologies, and cosmovisions that have the capacity to create new educational leadership frameworks that chart courses to visions beyond the current oppressive systems of education. Contributing authors discuss what does it look like to have thriving decolonial educational systems? What is the educational leadership that is needed and required to get us there? What does it look like from these global Indigenous and decolonial perspectives? How do we begin dismantling dominant and colonial systems, structures and styles of leadership? Schooling and education in the wake of ongoing colonial injustices requires a revolutionary (re)awakening and the creation of schooling and educational systems that inherently honour the sacredness of life on this Earth, beyond the anthropocentric. The centring, reclamation and reaffirmation of global counter and Indigenous knowledges in educational leadership is not an individual, nor isolated endeavour. Through this understanding, this anthology is centred around themes of schooling, community building, liberatory praxis and decolonial movements, and Indigenous governance.
Keywords: Educational leadership.; Inclusive education.; Indigenous peoples -- Education.; Education -- Leadership.; Educational strategies & policy.; elektronické knihy; electronic books